New insights into the use of a mite count reduction test for the detection of therapeutic acaricide efficacy in Psoroptes ovis in cattle. (December 2020) - van Mol, Wouter; Claerebout, Edwin; Casaert, Stijn; Geldhof, Peter; Levecke, Bruno
Abstract: When used for the evaluation of drug efficacy against Psoroptes ovis, the diagnostic performance of different sampling strategies for a mite count reduction test (MCRT) remains unclear. In the present study, a novel simulation framework was constructed that accounted for relevant biological features of P. ovis infestations in cattle and that was parameterized with field data from 16 farms (154 animals). Second, this framework was applied to explore the impact of study specific factors (number of animals, number of sampled lesions, and number of scrapings per lesion) and biological factors (mite infestation intensity and size of lesions) on the diagnostic performance of MCRT. Its outcome provided a basis to determine the diagnostic performance of MCRT when it was applied according to the World Association for the Advancement in Veterinary Parasitology (WAAVP) and the European Medicine Agency (EMA) guidelines, and to formulate recommendations to ensure a good diagnostic performance of the MCRT. For both guidelines, the MCRT allowed to correctly detect (power 80%) reduced and normal efficacy when the therapeutic efficacy was <70%, and ≥95%, respectively. The results highlighted a reliable diagnostic performance of the MCRT when performed as recommended by WAAVP and EMA for the detection of normal drug efficacy. When used for the detection of reduced efficacy, therapeutic efficacies between 70% and 90% could not be detected with sufficient reliability. The diagnostic performance can be improved by increasing the total number of skin scrapings (increasing the number of animals, number of sampled lesions and/or number of samples per lesion). In order to help researchers and veterinarians to optimize the design of the MCRT to their field settings, the findings were translated into a simple tool. Graphical abstract: Image 1 Highlights: Simulation framework for drug efficacy evaluation against Psoroptes ovis . WAAVP and EMA guidelines reliable for detection of normal efficacy; reduced efficacy unreliable. The total number of samples taken per farm and mite infestation intensity increase reliability. Summarizing tool for a wide variety of sampling strategies with resulting diagnostic performance.